INVESTIGATING EFL STUDENTS’ PERCEPTION ON ONLINE LEARNING AMIDST COVID-19 PANDEMIC - Tanjung, Firima Zona; Utomo, Aries (IJIET (International Journal of Indonesian Education and Teaching), 2021)
COVID-19 pandemic has resulted in the shifting of teaching-learning process from the combination of F2F and online learning to full-online one. This study aims to investigate students’ perspective on the implementation of full-online learning mode in English classroom with a low-tech environment. Employing convenience sampling, 104 university students participated in this study. Survey method was utilized. The findings showed that (1) the respondents have had various level of familiarity using search engine, social media, e-resources and learning apps that enable them to comprehend the learning content; (2) the use of social media, e-resources and learning apps results a different impact on respondents’ perception on learning effectiveness; (3) the respondents are more digitally-literate in using learning application or other online-based platforms and enable to autonomously learn the course materials as well as improve their language skills; (4) support system needs to be increased to engage students in teaching and learning activities; (5) there is a requirement of feedback and consistency in determining course schedule and timeline for task and exam submission. It can be concluded that university students have positive and negative perspective on full-online learning mode. Suggestions are presented in the closure.